Single molecule fluorescence measurements of complex systems - Sadegh, Sanaz, author; Krapf, Diego, advisor; Tamkun, Michael, committee member; Chong, Edwin, committee member; Prasad, Ashok, committee member (Colorado State University. Libraries, 2017)
Single molecule methods are powerful tools for investigating the properties of complex systems that are generally concealed by ensemble measurements. Here we use single molecule fluorescent measurements to study two different complex systems: 1/ƒ noise in quantum dots and diffusion of the membrane proteins in live cells. The power spectrum of quantum dot (QD) fluorescence exhibits 1/ƒ noise, related to the intermittency of these nanosystems. As in other systems exhibiting 1/ƒ noise, this power spectrum is not integrable at low frequencies, which appears to imply infinite total power. We report measurements of individual QDs that address this long-standing paradox. We find that the level of 1/ƒβ noise for QDs decays with the observation time. We show that the traditional description of the power spectrum with a single exponent is incomplete and three additional critical exponents characterize the dependence on experimental time. A broad range of membrane proteins display anomalous diffusion on the cell surface. Different methods provide evidence for obstructed subdiffusion and diffusion on a fractal space, but the underlying structure inducing anomalous diffusion has never been visualized due to experimental challenges. We addressed this problem by imaging the cortical actin at high resolution while simultaneously tracking individual membrane proteins in live mammalian cells. Our data show that actin introduces barriers leading to compartmentalization of the plasma membrane and that membrane proteins are transiently confined within actin fences. Furthermore, superresolution imaging shows that the cortical actin is organized into a self-similar fractal.